(untitled) (Journal of Technical and Vocational Education and Training, 2026)
Theatre technicians are an important yet under-documented workforce in the Nepali performing arts sector, where recognition of informal learning pathways by the formal TVET system is yet to be acknowledged. This gap limits insights into professional development and implications for productive TVET. So, this study employed a thematic literature review of 14 peer-reviewed articles, reports, and institutional sources from global, South Asian, and Nepal contexts, along with contextual practitioner knowledge. Following Braun and Clarke’s (2006) six-phase thematic analysis, the study identified a blend of institution-based and informal community-based or led learning pathways. The study identified strong intrinsic motivational factors like satisfaction from problem-solving, community belonging, etc., tempered by the extrinsic limitations like weak institutional support and lack of a formal system for developing professionalization. The findings revealed that learners’ unique competencies develop in situated production environments despite barriers. Finally, this paper proposes an integrative and innovative ecology in the Nepali performing arts sector that balances the benefits offered by informal community-based learning with vocational certification for gainful employment.